Diabetes and stroke potentiate hippocampal inhibitory tone: A link to Alzheimer's disease/vascular dementia: Development of new models and analysis methods/novel assays and technologies. (7th December 2020) - Buitrago, Luna; Li, Jei; Neymottin, Samuel; Barone, Frank; Brickman, Adam M.; Luchsinger, Jose; Moreno, Herman
Abstract: Background: Mice expressing mutated hAPP in the entorhinal cortex (EC) display, hypersynchrony of the EC‐hippocampus circuit, caused by decreased inhibitory tone (Angulo et al., NBD 2017). A similar EC inhibitory failure was also observed in mice expressing hAPOE4, (Nuriel et al., Nat Neursc 2017). Here we evaluated changes in EC‐hippocampus synaptic plasticity and neuronal properties produced by two additional AD risk factors, diabetes and ischemic stroke Method: Hippocampal synaptic plasticity and single cell recordings were made from leptin mutant (db/db, diabetes) and normoglicemic (db/+) heterozygous mice 4‐6 m.o. one month following stroke (transient middle cerebral artery occlusion (tMCAo) or sham surgery. tMCAo was produced by a monofilament occluding the origin of MCA for 30 minutes. Recordings were made from horizontal hippocampal slices in aCSF. Schaffer collaterals to CA1 evoked field excitatory postsynaptic potential (fEPSPs) were measured before and after induction of long term potentiation (LTP). Finally, miniature inhibitory post‐synaptic currents (mIPSCs) in CA1 pyramidal neurons were recorded, using the whole cell configuration of patch‐clamp technique. Result: Both control and diabetic mice developed a paradoxical larger LTP at the CA3‐CA1 synapse after stroke (i.e. db/db‐sham vs. db/db‐stroke, % of slope EPSP change = 180+/−21% vs. 250+/−16% respectively, p < 0.05. Modeling with the program NEURON simulator suggested that this was due to loss of synaptic inhibition. We found that the peak amplitude of mIPSCs was smaller in CA1 neurons in the stroked hemisphere compared to the sham CA1 hemisphere in db/+ mice (db/+ sham vs. db/+ tMCAo = ANOVA; F = 14, 99, p = 0.01). By contrast, CA1 mIPSCs frequency, but not amplitude, decreased in db/db tMCAo compared with db/db sham (F = 6.4, p = 0.022). The mean peak amplitude in db/db sham mice were significantly smaller than in db/+ sham mice (F = 6, 2, p = 0.021) Conclusion: The data suggest that the observed difference in sham vs. tMCAo mIPSCs amplitude observed in db/+ mice is due to a post‐synaptic change in either GABA‐A receptor number or function. While, in db/db sham mice we observed a post‐synaptic inhibitory alteration, as seen in db/+ mice with stroke. After acute ischemia, an additional presynaptic inhibitory dysfunction in db/db occurs. Modeling suggests that the mechanism occurs via inhibitory synaptic pruning.